Zasada pomocniczości w katolickiej nauce społecznej - Klimkowski, Michał (Społeczeństwo, 2022)
The ideas associated with the principle of subsidiarity developed by thinkers of liberalism, lived to see the continuation of the newly established thoughts in the twentieth century doctrine. The Catholic Church through its involvement in social issues contributed to the creation of the Catholic Doctrine, relating to society and the state. Its participation in the development of the idea of subsidiarity is so great that the Catholic Church is recognized today as it source. The current construction of the principle of subsidiarity is derived from the two papal encyclicals: Rerum novarum and Quadragesimo anno.